Heparan sulfate proteoglycans : key mediators of stem cell function - Ravikumar, Maanasa (2020)
Heparan sulfate proteoglycans (HSPGs) are an evolutionarily ancient subclass ofglycoproteins with exquisite structural complexity. They are ubiquitously expressedacross tissues and have been found to exert a multitude of effects on cell behaviorand the surrounding microenvironment. Evidence has shown that heterogeneity inHSPG composition is crucial to its functions as an essential scaffolding componentin the extracellular matrix as well as a vital cell surface signaling co-receptor. Here,we provide an overview of the significance of HSPGs as essential regulators of stemcell function. We discuss the various roles of HSPGs in distinct stem cell typesduring key physiological events, from development through to tissue homeostasisand regeneration. The contribution of aberrant HSPG production to altered stemcell properties and dysregulated cellular homeostasis characteristic of cancer is alsoreviewed. Finally, we consider approaches to better understand and exploit themultifaceted functions of HSPGs in influencing stem cell characteristics for cell therapyand associated culture expansion strategies.